2004
DOI: 10.1007/s11243-004-5162-9
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) catalyzed oxidation of cyclic ketones by cerium(IV)

Abstract: IrCl 3 which is considered to be a sluggish catalyst in alkaline media, was found to surpass the catalytic efficiency of even osmium and ruthenium in acidic media in the oxidation of cyclopentanone and 2-methylcyclohexanone by cerium(IV) sulphate in aqueous sulphuric acid medium. It was observed that the order of the reaction shows direct proportionality with respect to low concentrations of the oxidant and alcohols, but tends to become independent of concentration at higher concentrations. On increasing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Iridium(III) chloride has been reported to catalyze the oxidation of organic compounds in acidic medium [8][9][10][11]. To our knowledge, there have been only three uncatalyzed kinetic studies [12][13][14] of the reaction of arsenic(III) with hexacyanoferratre(III) in aqueous alkaline medium and the catalyzed study of the reaction has not been reported till now which prompted us to investigate the kinetics of this reaction both in the presence as well as in the absence of iridium(III) chloride.…”
Section: Introductionmentioning
confidence: 99%
“…Iridium(III) chloride has been reported to catalyze the oxidation of organic compounds in acidic medium [8][9][10][11]. To our knowledge, there have been only three uncatalyzed kinetic studies [12][13][14] of the reaction of arsenic(III) with hexacyanoferratre(III) in aqueous alkaline medium and the catalyzed study of the reaction has not been reported till now which prompted us to investigate the kinetics of this reaction both in the presence as well as in the absence of iridium(III) chloride.…”
Section: Introductionmentioning
confidence: 99%
“…Iridium(III) chloride has been reported to catalyze the oxidation of organic and inorganic compounds [1][2][3][4][5][6][7][8] in acidic [1][2][3][4][5][6] and alkaline [7,8] medium, while hexachloroiridate(IV) has been used as an oxidant for organic [9,10] and inorganic [11,12] compounds. Catalytic nature of iridium(III) chloride in the oxidation of organic compounds by alkaline hexacyanoferrate(III) [7,8,13] was not given much attention due to its sluggish behaviour in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%